Linguistic Research: Methods and Motives - James T. Collins (Masyarakat Linguistik Indonesia, 2026)
Before the late nineteenth century, linguistic research relied heavily on dictionaries, but by the end of the century two European scholars, G. Wenker and J. Gillieron, revolutionized linguistic methodology with two very different approaches to data collection in Europe. One hundred years later, just a few years before the founding of Masyarakat Linguistik Indonesia, two other European linguists, G. Diffloth and B. Nothofer, began their fieldwork projects in Island Southeast Asia. Their methodologies—connected yet differing in some details—have been explained in print and online sources. This essay focuses on linguistic fieldwork and research methodology based on empirical and inductive principles by reviewing the methods of Diffloth and Nothofer and comparing their approaches to those procedures used in a few recent linguistic studies of local languages in Malaysia and Indonesia. The underlying importance of studying the social history and the geography of the language communities involved in research projects as well as the need for cooperative interaction between researchers and language informants are the only basis for credible linguistic analysis. As hundreds of regional languages in Southeast Asia are threatened with obsolescence, linguists must not only document these languages but explore modes of cooperation with communities seeking to maintain their heritage languages from generation to generation. Computer programs such as ELAN can be used not only to document endangered languages but to revitalize them as well. As linguists, we need to rethink our procedures and enhance our interactions with the language communities of these islands.